1994
DOI: 10.1038/npp.1994.29
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Regulation of [125I]Iodocyanopindolol-labeled 5-Hydroxytryptamine1B Receptor Binding Sites in the Central Nervous System

Abstract: Little is known about the regulation of 5-hydroxytryptaminelB (5-HT1B) receptors, a putative terminal autoreceptor in the central nervous system. We studied the regional responses of [ 1 25IJiodocyanopindolol ([ 1 25!]ICYP)-labeled central 5-HT1B sites to chronic treatment with 5-HT agonists and antagonists at a dose of 10 mglkgld IP for 30 consecutive days in the rat. In controls, there were 3.4-fold regional differences in Bmax , with a rank order of brainstem > hippocampus> cortex, striatum> spinal cord, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The biphasic response to RU 24969 observed during abstinence from cocaine may have resulted from cocaine‐induced changes in interstitial 5‐HT concentrations, since adaptations in 5‐HT 1B receptor function are known to occur following prolonged elevations or decrements in extracellular 5‐HT levels. For example, chronic 5‐HT 1B receptor stimulation decreases the number of 5‐HT 1B binding sites in several brain structures (Pranzatelli and Razi 1994) and produces tolerance to the behavioral effects produced by 5‐HT 1B receptor agonists (De Souza et al . 1986; Oberlander et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biphasic response to RU 24969 observed during abstinence from cocaine may have resulted from cocaine‐induced changes in interstitial 5‐HT concentrations, since adaptations in 5‐HT 1B receptor function are known to occur following prolonged elevations or decrements in extracellular 5‐HT levels. For example, chronic 5‐HT 1B receptor stimulation decreases the number of 5‐HT 1B binding sites in several brain structures (Pranzatelli and Razi 1994) and produces tolerance to the behavioral effects produced by 5‐HT 1B receptor agonists (De Souza et al . 1986; Oberlander et al .…”
Section: Discussionmentioning
confidence: 99%
“…The biphasic response to RU 24969 observed during abstinence from cocaine may have resulted from cocaineinduced changes in interstitial 5-HT concentrations, since adaptations in 5-HT 1B receptor function are known to occur following prolonged elevations or decrements in extracellular 5-HT levels. For example, chronic 5-HT 1B receptor stimulation decreases the number of 5-HT 1B binding sites in several brain structures (Pranzatelli and Razi 1994) and produces tolerance to the behavioral effects produced by 5-HT 1B receptor agonists (De Souza et al 1986;Oberlander et al 1987;Frances and Monier 1991;Callaway and Geyer 1992). Because cocaine self-administration produces sustained elevations in extracellular 5-HT concentrations sufficient to stimulate 5-HT 1B receptors (Macor et al 1990;Parsons et al 1995), the blunted behavioral response to RU 24969 observed immediately following cocaine self-administration may reflect a down-regulation of 5-HT 1B receptor number or a decrease in the efficacy of their G-protein coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Extended cocaine self-administration results in robust decrements in ambient extracellular 5-HT levels ) and a substantial literature indicates an inverse relationship between 5-HT levels and 5-HT 1B binding density and/ or sensitivity (Weissmann et al 1986;Offord et al 1988; Van de Kar et al 1989;Crino et al 1990;Frankfurt et al 1993;Manrique et al 1993Manrique et al , 1994Pranzatelli and Razi 1994). Thus it may be that 5-HT 1B receptor function is enhanced following chronic cocaine exposure, a proposal which is supported by recent endocrinological studies (Levy et al 1992).…”
Section: Effect Of 8-oh-dpat On Gbr-12909 Self-administrationmentioning
confidence: 97%
“…22 5-HT 1B binding sites were detected using [ 125 I]-iodocyanopindolol. 23 Briefly, frozen brain sections were thawed and equilibrated in wash buffer (50 mM Tris, pH 7.4, 4 mM CaCl 2 , 0.01% ascorbic acid) at room temperature for 15 min. The slides were then incubated for 90 min at room temperature with 0.5 nM [ 125 I]-iodocyanopindolol in wash buffer containing pargyline (10 M) to inhibit monoamine oxidase degradation of the radioligand, DPAT (10 M) to block 5-HT 1A receptors, and isoproterenol (30 M) to block ␤ receptors.…”
Section: Methodsmentioning
confidence: 99%